Analisis Potensi Permintaan (Demand) Trans Siginjai Rute Telanai Pura - Sengeti - Muhammad Padri; Ade Nurdin; Dyah Kumalasari (Jurnal Talenta Sipil, 2022)
Jambi City is the capital city of Jambi Province as the center of government, education, business and trade. As a city center, it will certainly continue to develop. The mobility of the people certainly increases and causes movement, and the population continues to increase. Impact on increasing community economic and socio-cultural movements as well as community movement activities by transportation vehicles on road traffic. The operation of the trans Siginjai bus transportation mode with the aim of making it easier for people to reach places in urban areas and the buffer areas of the city of Jambi. The purpose of this study is to determine the characteristics of travellers and the choice of modes to determine the probability/potential demand (Demand) of trans siginjai by using the attributes of cost, travel time, waiting time, frequency of departure and level of comfort with stated preference method using 4 scenarios. Based on the results of the research, the probability/potential (Demand) of trans siginjai in scenario 1 is 79.7%, while private cars are 20.3%. In scenario 2, trans siginjai is 70.4% while private cars are 29.6%. In scenario 3 trans siginjai is 72.3% while private cars are 27.7%. In scenario 4, trans siginjai is 67.2% while private cars are 32.8%. From all the attributes of the transportation mode scenario, the probability/potential of the trans siginjai is greater than that of a private car and also from the 4 scenarios, the percentage of scenario 1 is greater than the other scenarios.